2018
DOI: 10.2147/ijn.s172907
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology, from quantum mechanical calculations up to drug delivery

Abstract: There are several reasons why nanotechnology is currently considered as the leader among the most intensively developing research trends. Nanomatter often exhibits new properties, other than those of the morphology of a continuous solid. Also, new phenomena appear at the nanoscale, which are unknown in the case of microcrystalline objects. For this reason, nanomaterials have already found numerous applications that are described in this review. However, among intensively developed various branches of nanotechn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 167 publications
(191 reference statements)
1
17
0
Order By: Relevance
“…There are many types of these structures, among which only those have been used which have functional groups that allow attachment of CisPt ( Figure 3). ful_308a4 ful_308b4 Despite the initially expected chemical inactivity of C60 and its derivatives, it was found that fullerenes can be functionalized [21]. Due to the mode of functionalization, there were distinguished exo-and endohedral forms of fullerenes and heterofullerenes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many types of these structures, among which only those have been used which have functional groups that allow attachment of CisPt ( Figure 3). ful_308a4 ful_308b4 Despite the initially expected chemical inactivity of C60 and its derivatives, it was found that fullerenes can be functionalized [21]. Due to the mode of functionalization, there were distinguished exo-and endohedral forms of fullerenes and heterofullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the mode of functionalization, there were distinguished exo-and endohedral forms of fullerenes and heterofullerenes. The essence of Despite the initially expected chemical inactivity of C 60 and its derivatives, it was found that fullerenes can be functionalized [21]. Due to the mode of functionalization, there were distinguished exo-and endohedral forms of fullerenes and heterofullerenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of targeted therapy is frequently related to immobilization of drug molecules by molecular carriers. Such a role can be fulfilled by different classes of molecules like albumin [1], chitosan [2,3], gelatin [4], gold complexes [5,6], hydrogels [7], magnetic iron oxides [8] polymers [9][10][11], cube rhombellanes [12][13][14] and fullerenes and their derivatives [15][16][17][18]. The implementation of such types of methods ensures the direct delivery of drugs and their release to the appropriate biological target.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one of the most dynamically developing groups of nanoparticles, applicable not only in medicine and pharmacy, are fullerenes. One of the most commonly used molecules in this group is fullerene C60 [15][16][17][18]22]. The characteristic chemical structure of this molecule increases the binding capacity toward biologically active molecules containing aromatic systems.…”
Section: Introductionmentioning
confidence: 99%